Human Capital–Driven Digital Transformation Strategy to Strengthen Organizational Resilience in Immigration Institutions in the Era of Society 5.0 (International Forum of Researchers and Lecturers, 2025)
This study explores the strategic alignment of digital transformation and human capital development as a foundation for enhancing organizational resilience within immigration institutions in the context of Society 5.0. As public sector entities, immigration agencies are under increasing pressure to respond to technological advancements and socio-political volatility while ensuring service excellence and maintaining national security. A key issue identified is the lack of sustainability in digital initiatives when workforce capabilities and digital literacy are insufficiently addressed. The research aims to establish a conceptual framework that highlights the importance of human-centered digital transformation in strengthening the adaptive capacity of immigration institutions. Using a narrative literature review approach, the study integrates empirical evidence, theoretical perspectives, and policy insights to analyze the connections among digital transformation, human capital, digital skills, and organizational resilience. The findings indicate that successful digital transformation extends beyond technological upgrades; it requires continuous investment in employee competencies, digital literacy, and organizational culture shifts. Enhanced digital literacy among staff is linked to better decision-making, increased innovation, and agile crisis response. Additionally, participatory approaches to change management foster greater employee involvement and support long-term adaptability. The study concludes that a comprehensive digital transformation strategy—grounded in the development of human capital—is essential for building resilient public organizations capable of navigating the complexities of Society 5.0. These insights offer practical guidance for public sector leaders and policymakers on aligning digital investments with workforce development, institutional learning, and inclusive change processes. Emphasizing the human dimension of digital transformation ensures that immigration agencies are not only technologically equipped but also culturally and operationally prepared to thrive in an increasingly digital and uncertain world.